PERANCANGAN UI/UX APLIKASI PEREKRUTAN KARYAWAN PT RODA PRIMA PERKASA MENGGUNAKAN METODE DESIGN THINKING - Vicinsky Owen Tanner; Wilbert Anderson; Darriel Dapples; Lionnell Julycell Huang; Ahmad Farisi; Nora Hafildah (Jurnal Riset Sistem Informasi, 2026)
PT Roda Prima Perkasa, a building materials distributor, still uses a conventional employee recruitment process based on paper and email, which leads to inefficiencies such as lengthy file selection, risk of data loss, recording errors, and difficulties in data management. This study aims to design a User Interface (UI) and User Experience (UX) for an employee recruitment application to improve the effectiveness and efficiency of the recruitment process. The Design Thinking method was applied, consisting of five stages: empathize, define, ideate, prototype, and test. A qualitative approach was used through interviews with outsourcing personnel as system users to identify user needs and constraints. The results show that the proposed UI/UX design focuses on user needs, provides a clear workflow, and simplifies applicant data management, thereby improving recruitment efficiency, reducing errors, and enhancing user experience for both the company and applicants